Aspectos legais da expansão urbana sobre as áreas e usos rurais na Região Metropolitana de Belo Horizonte - Mateus Almeida Nunes (2019)
Based on a study carried out during my work as head of the Metropolitan Regulation Board at the Metropolitan Region of Belo Horizonte Agency - RMBH Agency, regarding the Executive Plans elaborated from 2005 in the Metropolitan Region of Belo Horizonte, I noticed a great deficiency of the texts in relation to the proposals, programs and actions directed to the planning of the areas and rural uses. In addition to this we have extremely permissive municipal legislations regarding to new urban expansions and rural / urban conversions that have made possible a highly fragmented urban fabric. Due to this, the main focus of this dissertation is the analysis of the federal, state and municipal urban planning laws that govern the processes of urban expansion and territorial planning, in order to ascertain the possible impacts on the rural environment, as well as to try to understand the reasons that led the Master Plans not to deepen into the rural dynamics. The Statute of the City, Federal Law 10,257/2001, will have a greater emphasis, since much of the existing content in the Municipal Master Plans derives from its text, legal provisions and instruments, guided the entire participatory process of production of municipal legislation. In order to achieve this analysis, it’s first necessary to present a retrospective on the process of industrialization / urbanization in Brazil that resulted in the metropolization of several urban centers, with deepening in the Metropolitan Region of Belo Horizonte. Besides exposing as well, a contextualization on the current theoretical fronts that study the new configuration of rural pluriactivities in integration and complementarity with the urban issues. Finally, the dissertation will present some reflections about the limitations existing in the development and integration of rural areas and uses, as well as some proposals to change the scenario presented throughout the dissertation.